"Do not detach the placenta from my baby's cord" - Lotus birth case series from Tanzania tertiary hospital. (October 2022) - Kyejo, Willbroad; Rubagumya, Davis; Mwalo, Christian; Moshi, Lynn; Kaguta, Munawar; Mgonja, Miriam; Jaiswal, Shweta
Abstract: Introduction: Lotus birth is seldom practiced, with its prevalence being not well documented. There is no clear existing guideline or pathway for this practice. Safety in delivery as well as caring for newborn and her mother is of paramount importance. Hence, clarity for Lotus delivery in any set up is indispensable. Cases findings: We have described on case series approach to women who opted to delivery without detachment of placenta. We have described delivery characteristics, neonatal clinical course, cord, and placenta management. In year 2022 at our center, we have received two cases of lotus delivery. Conclusion and recommendation: Lotus birth is a new way of delivery in our country despite of low prevalence, it is indispensable for all cadres that deal with delivering mothers to be aware for better outcomes. It has been noted that, the risk for neonatal infection increases with this practice. Highlights: Lotus birth in Tertiary hospital Rare case series of umbilical nonseverance Multidisciplinary approach